2009
DOI: 10.1161/circulationaha.108.800011
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Is Associated With Increased Long-Term Mortality After Cardiothoracic Surgery

Abstract: Background-Long-term survival after acute kidney injury (AKI) is poorly studied. We report the relationship between long-term mortality and AKI with small changes in serum creatinine during hospitalization after various cardiothoracic surgery procedures. Methods and Results-This was a retrospective study of 2973 patients with no history of chronic kidney disease who were discharged from the hospital after cardiothoracic surgery between 1992 and 2002. AKI was defined by the RIFLE classification (Risk, Injury, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

36
628
10
29

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 859 publications
(703 citation statements)
references
References 31 publications
36
628
10
29
Order By: Relevance
“…En el estudio de Hobson y colaboradores (16) se analizaron retrospectivamente 2.973 pacientes sin historia de ERC sometidos a cirugía cardíaca e igual que en el presente estudio se utilizó la clasificación RIFLE para definir IRA. La sobrevida fue menor en los pacientes que presentaron deterioro de la función renal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En el estudio de Hobson y colaboradores (16) se analizaron retrospectivamente 2.973 pacientes sin historia de ERC sometidos a cirugía cardíaca e igual que en el presente estudio se utilizó la clasificación RIFLE para definir IRA. La sobrevida fue menor en los pacientes que presentaron deterioro de la función renal.…”
Section: Discussionunclassified
“…El desarrollo de IRA, a su vez, se asocia a complicaciones infecciosas de gravedad variable, incremento en la estadía hospitalaria y mal pronóstico a largo plazo con aumento significativo de la mortalidad (1,4,6,9,15,16) . Considerando todo lo previamente expuesto, los objetivos del trabajo fueron determinar la incidencia acumulada de IRA en el POCC en nuestro servicio, evaluar la existencia de predictores de IRA y mortalidad asociada.…”
Section: Introductionunclassified
“…41 Several studies have demonstrated that postoperative acute kidney injury, even after it was resolved, was associated with increased risks for chronic kidney disease, hemodialysis and death years after surgery. 9,10,[42][43][44] Other serious postoperative complications like mechanical ventilation and sepsis are also associated with increased long-term mortality and development of chronic critical illness and disability. [45][46][47] Hence postoperative complications can affect a diverse group of patients imposing an acute burden of death and suffering, and even after resolved can affect future health and quality of life mandating that follow-up of these patients occur in prolonged and more structured manner.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5 Acute kidney injury (AKI) is a common postoperative complication, and our group has shown that small changes in serum creatinine are associated with increased hospital and intensive care unit lengths of stay as well as hospital and ninety-day mortality rates after major surgery. [7][8][9][10] With the emergence of consensus criteria to standardize the definition of this postoperative complication, especially with mild and moderate degrees of AKI, recent studies within the vascular literature have demonstrated that AKI prevalence ranges from 13%-76% and is associated with adverse perioperative outcomes. [11][12][13][14] Many of these studies have focused on the prevalence of AKI after a specific procedure using small patient cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Известно, что развитие ОПП после кардиохирур-гических вмешательств с использованием искус-ственного кровообращения (ИК) значительно ухуд-шает ближайший и отдаленный прогноз [9,12,15,16]. При этом значительно увеличивается частота сердечно-сосудистых осложнений и острой почеч-ной недостаточности, госпитальная летальность колеблется от 6% до 32,5%, а также растет пропор-ция больных, нуждающихся в программном гемоди-ализе [8,[15][16][17].…”
unclassified